2013
DOI: 10.1063/1.4816291
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the primary instability in a separated boundary layer transition under elevated free-stream turbulence

Abstract: Numerical studies of laminar-to-turbulent transition in a separation bubble subjected to two free-stream turbulence levels (FST) have been performed using Large-Eddy Simulation (LES). Separation of the laminar boundary layer occurs at a curvature change over a plate with a semi-circular leading edge at Re = 3450 based on the plate thickness and the uniform inlet velocity. A numerical trip is used to produce the targeted free-stream turbulence levels and the decay of free-stream turbulence is well predicted. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 28 publications
6
32
0
Order By: Relevance
“…By increasing the level of FSTI, the transition process in the separated shear layer is promoted, leading to earlier mean flow reattachment [53,143] and thus a reduction in the size of the separation bubble. This finding has been confirmed more recently by Lamballais et al [138,139] who simulated the flow over a blunt flat plate with rounded corners using DNS, as well as by Langari and Yang [140] who simulated the flow over a blunt nosed flat plate using Large Eddy Simulations (LES). Lamballais et al [139] showed that the reduction in separation bubble length is more significant for larger corner radii of the plate since a larger separation bubble initially forms at low FSTI, and thus the observed reduction at elevated FSTI is more significant.…”
Section: Laminar Separation Bubblesmentioning
confidence: 54%
See 3 more Smart Citations
“…By increasing the level of FSTI, the transition process in the separated shear layer is promoted, leading to earlier mean flow reattachment [53,143] and thus a reduction in the size of the separation bubble. This finding has been confirmed more recently by Lamballais et al [138,139] who simulated the flow over a blunt flat plate with rounded corners using DNS, as well as by Langari and Yang [140] who simulated the flow over a blunt nosed flat plate using Large Eddy Simulations (LES). Lamballais et al [139] showed that the reduction in separation bubble length is more significant for larger corner radii of the plate since a larger separation bubble initially forms at low FSTI, and thus the observed reduction at elevated FSTI is more significant.…”
Section: Laminar Separation Bubblesmentioning
confidence: 54%
“…However, at increased levels of FSTI, the spanwise coherence of shear layer rollers at the roll-up location is decreased notably [31,32], as compared to experiments performed in low disturbance environments [18,133] or simulations [16]. At high levels of FSTI (greater than approximately 1-2%), notable streamwise velocity fluctuations are detected upstream of separation [140]. These fluctuations are indicative of bypass transition and, more specifically, are evidence of streamwise oriented streaks forming in the laminar boundary layer upstream of mean separation [16,37,133].…”
Section: Laminar Separation Bubblesmentioning
confidence: 81%
See 2 more Smart Citations
“…LES of Abdalla and Yang 18 on a blunt flat plate have observed that the transition in a separated shear layer occurs through inviscid mechanism and the transformation of the K-H rolls into threedimensional structures is most likely due to helical instability associated with pairing of vortices and breaking down to turbulence. LES of Langari and Yang 19 for a separation bubble produced on the semi-circular leading edge of a flat plate for different levels of free stream turbulence observed that at low free stream turbulence level the separated layer undergoes transition via K-H mechanism, while at high free stream turbulence levels K-H mechanism is bypassed. Recent experimental and computational studies to demonstrate the effect of low Re operation of NACA64A006 and NACA2415 aerofoils has been carried out by Genc et al [20][21][22] Their studies illustrate the formation of separation bubble its transition and reattachment at various angles of attack and associated stall characteristics.…”
Section: Introductionmentioning
confidence: 99%